Aircraft cabin easy-mover equipment - Shaikha Thurayya Taha Mattar (Nanyang Technological University, 2020)
In today's world, the high demand of travel by air continues to be an important mode of transporting people and cargo from one destination to another in the quickest fashion. Aircrafts are designed to fly, thus, it is vital to minimise their downtime and maximise their capability to fly without compromising the safety of its passengers, flight and cabin crews. During my professional years of experience as an Aircraft Maintenance Engineer, I recognise the need to innovate an equipment designed specifically for maintenance use within the aircraft cabin interior. Hence, this report focuses on exploring the various designs of lifting devices that are available in the market. A thorough study of the current designs was analysed and derived to a final design that combines the possibility to be innovative with an aim to reduce resources, manpower, time and most importantly, cost. The proposed design of an Aircraft Cabin Easy-Mover Equipment consists of rectangular shaped solid base with cut-outs in the mid-section. Ball Transfer Units are embedded onto the top surface of the main body structure that allows movement or rotation of cabin components. Swivel Castor Wheels are installed at the bottom surface of the equipment. Handles are incorporated at the rear while at the forward side the equipment are designed with slopes. This equipment is suitable for various cabin maintenance use that is capable to accommodate the different shapes, sizes and weight of each cabin component where it would be a perfect fit for newer designs aircraft cabin interior with composite based components.